New addition of Barleria prionites L. (Acanthaceae) to the flora of Nepal - Bhatt, GD; Kurmi, PP; Baral, SR (Banko Janakari, 2010)
DOI: 10.3126/banko.v20i1.3509 Banko Janakari, Vol. 20, No. 1 pp.51-52